Imaging spinal neuron ensembles active during locomotion with genetically encoded calcium indicators. (26th March 2013) - Hinckley, Christopher A.; Pfaff, Samuel L.
Abstract : Advances in molecular‐genetic tools for labeling neuronal subtypes, and the emerging development of robust genetic probes for neural activity, are likely to revolutionize our understanding of the functional organization of neural circuits. In principle, these tools should be able to detect activity at cellular resolution for large ensembles of identified neuron types as they participate in specific behaviors. This report describes the use of genetically encoded calcium indicators (GECIs), combined with two‐photon microscopy, to characterize V1 interneurons, known to be critical for setting the duration of the step cycle. All V1 interneurons arise from a common precursor population and express engrailed‐1 ( En1 ). Our data show that although neighboring interneurons that arise from the same developmental lineage and share many features, such as projection patterns and neurotransmitter profiles, they are not irrevocably committed to having the same pattern of activity.